Herpesviridae - Ongradi, Jozsef (IntechOpen, 2016)
Herpesviruses are unique among viruses as they encode for a complex self-regulatory system, aggressively invade and persist in the host, evade immune defense, alter all regulatory mechanisms of the macroorganism and modify the replication of heterologous viruses. Environmental factors influence these unconventional relationships. Consequently, a single herpesvirus species can be attributed to a wide range of diseases as etiological agents or cofactors. This book is intended to give an overview on selected clinical hot topics: herpes simplex virus encephalitis, persistent infection in the gingiva, thymidine kinase gene expression causing male infertility, and pharmaceutical reactivation of Epstein-Barr virus for oncolysis. Immune evasion mechanisms and new ways to formulate vaccines are exhaustively reviewed. Finally, a surprise: bovine herpesviruses could serve as models to study the pathomechanism of herpesviruses.